PERBAIKAN KUALITAS TEGANGAN MENGGUNAKAN DYNAMIC VOLTAGE RESTORER (DVR) - Winarso Winarso (Foristek, 2013)
Dynamic Voltage Restorer is one of quality solution methods of electric power that is used to recover drop voltage (sag) by injecting voltage to the network. Injection of minimum power method is minimum active power supplied to the load as compensation of sag. Thus, it can stabilize load voltage. The aim of this research is to maintain voltage magnitude constantly in the sensitive load location, when fault occur. In tackling sag and swell problems, DVR can solve balance and unbalance conditions by injecting appropriate voltage component. Therefore, the normal condition at source voltage can be achieved as soon as possible. DVR Control produces fast and accurate response that lead to an accurate solution increasing quality of electric power system caused by sag. Sag can disturb performance of sensitive equipments. MATLAB-SIMULINK withtoolbox of electric power system will be utilized in simulation process.